A high melt strength polyamide composition and a process for its preparation and use

Titanium dioxide treated with phosphite forms a micro-crosslinked network with polyamide, which solves the problem of insufficient melt strength of polyamide and achieves a combination of high melt strength and good flowability, making it suitable for injection molding, blow molding, extrusion and 3D printing.

CN122628532BActive Publication Date: 2026-11-06WANHUA CHEM GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611098220.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-11-06
Estimated Expiration
2046-07-23

AI Technical Summary

Technical Problem

The melt strength of existing polyamide materials is insufficient, which leads to problems such as surface cracking, unstable bubble tubes, melt sagging and bubble cell merging during processing, making it difficult to meet the high requirements of injection molding, blow molding, extrusion and 3D printing.

Method used

A composite of titanium dioxide with phosphite surface treatment and polyamide is used to construct a dynamically stable micro-crosslinked network structure through coordination complexation reaction, which improves melt strength while maintaining good processing fluidity.

Benefits of technology

It significantly improves the melt strength and molecular chain entanglement of polyamide, solving the problem of insufficient melt strength, while maintaining the processing fluidity and mechanical property stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a kind of high melt strength polyamide compositions and its preparation method and application, it is related to polyamide technical field, solve the problem that polyamide high melt strength and processing fluidity is difficult to give consideration to, long-term use is prone to performance attenuation.In the application, high melt strength polyamide composition raw material includes polyamide 75%~99.6% and functional auxiliary agent 0.2%~24.5% by mass percentage;Raw material also includes titanium dioxide treated by phosphite surface;In raw material, the mass percentage content of titanium dioxide treated by phosphite surface treatment titanium dioxide in the mass of 0.005%~0.6%;In titanium dioxide treated by phosphite surface treatment, the mass ratio of phosphite and titanium dioxide is (0.02~1):1;The particle size of titanium dioxide is 10~1000nm.The application provides polyamide melt strength while maintaining good processing fluidity, while having good performance stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polyamide technology, specifically to a high melt strength polyamide composition, its preparation method, and its application. Background Technology

[0002] Polyamide (nylon), as a class of high-performance engineering plastics, has been widely used in various fields such as automotive manufacturing, electronics, packaging materials, and engineering components due to its good mechanical strength, chemical resistance, abrasion resistance, and processing flowability. With the upgrading of industrial technology, the processing methods of polyamide are becoming increasingly diversified. Processes such as injection molding, blown film molding, blow molding, extrusion molding, foam plastic preparation, and 3D printing place higher demands on the melt properties of polyamide, among which melt strength is a key indicator determining processing stability and final product quality.

[0003] Melt strength essentially reflects the ability of a polymer melt to resist stretching and deformation during processing, and is directly related to the polymer's molecular weight, molecular weight distribution, and the degree of molecular chain entanglement. Traditional polyamides, due to their regular molecular chain structure and high linearity, have predominantly van der Waals forces as the inter-chain forces, resulting in limited entanglement and generally low melt strength (typically <80mN according to ISO 16790-2021 standards). This deficiency leads to a series of problems in actual processing: in injection molding, low melt strength causes surface cracking, resulting in surface defects; in blown film production, low melt strength leads to unstable and easily ruptured bubbles, making it impossible to produce films with uniform thickness; in hollow blow molding, severe melt sagging results in uneven product wall thickness and bottom collapse; in foaming processes, the melt cannot effectively encapsulate bubbles, leading to bubble merging and rupture, making it difficult to form a dense and uniform foam structure; in 3D printing, excessive melt flow can cause "stringing" and "collapse," affecting printing accuracy and interlayer bonding.

[0004] To address the problem of insufficient melt strength in polyamide, various improvement schemes have been proposed in the existing technology, mainly including the following categories: Chemical crosslinking modification: By adding chemical crosslinking agents such as peroxides and isocyanates, polyamide molecular chains undergo covalent crosslinking during processing to form a three-dimensional network structure. However, this method has significant drawbacks: the amount of crosslinking agent is difficult to control precisely; too little agent results in limited improvement in melt strength, while too much agent can lead to over-crosslinking, causing the material to become brittle and lose its processing fluidity; furthermore, the crosslinking reaction is irreversible, making subsequent recycling and processing difficult, which is inconsistent with the trend of green environmental protection.

[0005] Blending modification: Polyamide is blended with high melt strength polymers (such as polyethylene, polypropylene, polycarbonate, etc.) to improve melt strength by utilizing the entanglement of molecular chains in the blend. However, polyamide has poor compatibility with most polymers, requiring the addition of compatibilizers, which not only increases production costs but may also lead to a decrease in the mechanical properties of the material. At the same time, the phase separation problem in the blend system is difficult to completely solve, and performance degradation is likely to occur during long-term use.

[0006] Nanofiller modification: Adding nanofillers such as nano-calcium carbonate, montmorillonite, and carbon nanotubes to polyamides enhances molecular entanglement through the interaction between the filler and the molecular chain. However, traditional nanofillers have significantly different surface polarities from polyamides, resulting in poor dispersibility and agglomeration. This not only fails to form an effective network structure but also becomes an internal defect in the material, leading to minimal improvement in melt strength and reduced processing fluidity.

[0007] Molecular weight control: The absolute molecular weight of polyamide can be increased by optimizing the polymerization process, but excessively high molecular weight will lead to a sharp increase in melt viscosity, significantly increase processing difficulty, greatly increase energy consumption, and impose stringent requirements on equipment, making it difficult to achieve industrial production. Summary of the Invention

[0008] This application provides a high melt strength polyamide composition, its preparation method, and its application, to solve the problems in the prior art where it is difficult to balance high melt strength and processing fluidity of polyamides, and performance degradation is likely to occur during long-term use.

[0009] In a first aspect, this application provides a high melt strength polyamide composition, wherein the raw materials of the high melt strength polyamide composition, by mass percentage, include 75% to 99.6% polyamide and 0.2% to 24.5% functional additives; The raw materials also include titanium dioxide that has been surface-treated with phosphite; The mass percentage of titanium dioxide in the titanium dioxide surface-treated with phosphite is 0.005%~0.6%; In the titanium dioxide surface treated with phosphite, the mass ratio of phosphite to titanium dioxide is (0.02~1):1, preferably (0.5~1):1; The titanium dioxide surface treated with phosphite has a particle size of 10~1000nm, preferably 50~500nm.

[0010] This application uses titanium dioxide with phosphite surface treatment to enhance the interfacial interaction between titanium dioxide and polyamide. Then, through coordination complexation reaction and time-temperature equivalence principle, a dynamically stable micro-crosslinked network structure is constructed. The specific reaction mechanism is as follows: (1) Titanium dioxide surface activation: The P=O functional group in the phosphite molecule can undergo dehydration condensation reaction with the hydroxyl group (-OH) on the surface of titanium dioxide to form a stable chemical bond layer, which replaces the original adsorbed water and impurities on the surface of titanium dioxide, reduces the surface energy, and exposes more active Ti. 4+ Site, and at the same time, the hydrophobic groups (such as benzene rings and alkyl chains) in the phosphite molecule can improve the compatibility between titanium dioxide and the polyamide matrix, improve the dispersibility of titanium dioxide, and avoid agglomeration; (2) Coordination complexation reaction initiation: During the processing (temperature 170-340℃), the polyamide molecular chain is heated and the lone pair electron activity of N and O atoms in the amide bond is enhanced; the Ti surface of titanium dioxide after activation by phosphite 4+ The Lewis acid activity is significantly enhanced, which can efficiently coordinate with the N and O atoms in the amide bond of polyamide to form strong Ti-O and Ti-N coordination bonds. Each titanium dioxide particle can combine with multiple polyamide molecular chains to initially form micro-crosslinking nodes of "particle-molecular chain", ensuring that a dense micro-crosslinking network can be formed at low addition levels; (3) Micro-crosslinking network construction: As the processing progresses, a large number of micro-crosslinking nodes connect with each other to form a three-dimensional micro-crosslinking network structure. This structure is not an irreversible chemical crosslinking, but a physical-chemical combination network with coordination bonds as the core. It can significantly improve the degree of molecular chain entanglement and retain a certain degree of molecular chain fluidity, avoiding the embrittlement problem caused by excessive crosslinking; (4) Continuous strengthening driven by time-temperature equivalence: According to the time-temperature equivalence principle, temperature and time have equivalent effects on the movement of polymer molecules. During long-term use, even in a room temperature environment, the thermal motion of molecular chains can still provide enough energy to drive the coordination complexation reaction to continue: the amide bonds that did not participate in the initial reaction continuously interact with the activated Ti on the surface of titanium dioxide. 4+ Combined, new micro-crosslinking nodes are continuously generated, and the original coordination bonds are continuously optimized, making the micro-crosslinking network more compact and stable; (5) The essence of improved melt strength: the formation and improvement of the micro-crosslinking network significantly improves the effective molecular weight and molecular chain entanglement of polyamide, and reduces molecular chain slippage.

[0011] Based on the mass percentage of titanium dioxide in the phosphite-treated titanium dioxide, the mass percentage in the raw material is 0.005%~0.6%. When the content is below 0.005%, there are insufficient reaction sites, and an effective micro-crosslinked network cannot be formed, resulting in a low increase in melt strength. When the content is above 0.6%, the excess titanium dioxide is prone to agglomeration, which cannot be completely avoided even after phosphite treatment. This leads to a sharp increase in melt viscosity, deterioration of processing fluidity, and a continuous decrease in melt strength, proving that there is no melt strength improvement effect in this range.

[0012] Titanium dioxide has a particle size of 10~1000nm. The particle size of titanium dioxide is a key factor affecting its dispersibility and coordination complexation efficiency: if the particle size is too small (<10nm), it is easy to agglomerate and it is difficult to disperse uniformly in the polyamide matrix; if the particle size is too large (>1000nm), the specific surface area is reduced, the contact sites with the polyamide molecular chain are reduced, the coordination complexation reaction is insufficient, and a dense micro-crosslinked network cannot be formed.

[0013] The mass ratio of phosphite to titanium dioxide is (0.02~1):1. If the amount of phosphite is too low, it is difficult for it to form an effective activation and coating on the surface of titanium dioxide, which will affect the Ti... 4+ Insufficient activation of Lewis acid sites leads to weak coordination and complexation between titanium dioxide and the N and O atoms in the amide bond of polyamide, resulting in a limited improvement in reaction rate. Furthermore, the dispersibility of titanium dioxide in the polyamide matrix is ​​only slightly improved, and aggregation is likely to occur. When the amount of phosphite is too high, excessive phosphite will form an overly thick coating layer on the surface of titanium dioxide, shielding the Ti... 4+ Active sites hinder coordination and complexation with amide bonds, thus reducing the reaction rate. Simultaneously, an increase in free phosphite in the system easily triggers polyamide degradation during high-temperature processing, leading to decreased melt viscosity, deterioration of product mechanical properties, yellowing, and other adverse effects such as surface precipitation and decreased processing stability. Controlling the mass ratio of phosphite to titanium dioxide within the range of (0.02–1):1 can effectively improve the surface Ti content of titanium dioxide treated with phosphite. 4+ Lewis acid activity significantly enhances the rate of coordination complexation reaction between Lewis acid and polyamide amide bonds, while avoiding problems such as shielding of active sites and polyamide degradation, thus ensuring the comprehensive performance and processing stability of the composite material.

[0014] In some possible embodiments, the polyamide has a relative viscosity of 1.4 to 3.4, preferably 2.2 to 2.8. This relative viscosity range ensures good processing flowability of the composition while providing sufficient reaction sites for molecular chain entanglement and coordination complexation reactions, thus ensuring the formation of a micro-crosslinked network. As the matrix material of the composition, the nitrogen and oxygen atoms in the amide bonds (-CONH-) of the polyamide molecular chain both possess lone pairs of electrons, which can interact with the Ti atoms on the surface of titanium dioxide after phosphite surface treatment. 4+ The formation of strong coordination bonds provides a solid chemical basis for the construction of micro-crosslinked networks; at the same time, the excellent mechanical properties and chemical resistance of polyamide itself provide performance assurance for the final application of the composition.

[0015] The relative viscosity of polyamide was determined according to GB / T 12006.1-2009 (equivalent to ISO 307:2007): 96wt% concentrated sulfuric acid was used as the solvent. The polyamide was dried to constant weight at 105℃. A homogeneous sample solution with a polyamide concentration of 0.01 g / mL was precisely prepared using the polyamide and solvent, and allowed to stand to remove bubbles. A calibrated Ubbelohde capillary viscometer was placed in a constant temperature water bath at 25±0.1℃. The outflow time of the solvent (96wt% concentrated sulfuric acid) and the sample solution through the scale was measured separately. Each group was tested in triplicate, and the average value was taken. Relative viscosity η r =t / t0 (t is the sample solution outflow time, t0 is the solvent outflow time), and air bubbles should be avoided throughout the test.

[0016] In some embodiments, the polyamide includes repeating units -[NH-R1-CO]- and / or -[NH-R2-NH-CO-R3-CO]-; wherein R1, R2, and R3 are each independently selected from one or more of alkylene, alicyclic, and aromatic groups.

[0017] In some embodiments, the alkylene group is a C5-C12 alkylene group.

[0018] In some embodiments, the polyamide includes one or more of aliphatic polyamide, alicyclic polyamide, and semi-aromatic polyamide.

[0019] In some embodiments, the polyamide includes polydodecanolactam (PA12), polyundecanolactam (PA11), polydecanodicidediamine (PA1012), polydecanodicidehexamethylenediamine (PA612), polydecanodicidehexamethylenediamine (PA610), polycaprolactam (PA6), polyhexamethylene adipamide (PA66), polypentanediamine adipamide (PA56), polyhexadecanediamine (PA613), polyhexadecanediamine adipamide (PA513), polyhexadecanediamine adipamide (PA516), polydecanodicidedodecanediamine (PA1212), and poly[bis(3-methyl] [Bis(4-aminocyclohexyl)methane-alt-dodecanediamide] (MACM12), poly[bis(4-aminocyclohexyl)methane-alt-dodecanediamide] (PACM12), poly[bis(4-aminocyclohexyl)methane-alt-dodecanediamide] (PACM11), poly(m-phenylene adipamide) (MXD6), poly(hexamethylene terephthalamide) (PA6T), poly(hexamethylene terephthalamide) (PA6I), poly(nonadiamine terephthalamide) (PA9T), poly(decylamine terephthalamide) (PA10T), poly(dodecanediamine terephthalamide) (PA12T) or one or more of the following:

[0020] In some possible embodiments, the phosphite includes one or more of triphenyl phosphite, trioctyl phosphite, tri(2-ethylhexyl) phosphite, diphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol diphosphite (2,4-di-tert-butylphenol), and phenyl diisooctyl phosphite.

[0021] In some possible implementations, the titanium dioxide includes one or both of anatase titanium dioxide and rutile titanium dioxide.

[0022] In some possible implementations, the functional additives include one or more of the following: dispersants, antioxidants, light aging resistant additives, heat stabilizers, lubricants, antistatic agents, fillers, pigments, flame retardants, plasticizers, and toughening agents.

[0023] In some possible implementations, the plasticizer includes N-butylbenzenesulfonamide (BBSA); In some possible implementations, the toughening agent comprises maleic anhydride-grafted polyolefin elastomer (MH5040). In some possible implementations, the functional additives include dispersants and antioxidants. The combination of dispersants and antioxidants can optimize the processing properties, stability, and performance characteristics of the composition. In some possible implementations, the dispersant includes one or more of the following: silane coupling agent, calcium stearate, zinc stearate, polyethylene wax, polypropylene wax, montan wax, rice bran wax, and vinyl bis-stearamide. In some possible embodiments, the silane coupling agent comprises one or more of γ-aminopropyltriethoxysilane (KH550), 3-glycidoxypropyltrimethoxysilane (KH560), and γ-methacryloyloxypropyltrimethoxysilane (KH570); In some possible implementations, the mass content of the dispersant is 0.02-3% based on the total mass of the raw materials of the high melt strength polyamide composition.

[0024] Dispersants can reduce the surface energy of titanium dioxide, improve its dispersibility in the polyamide matrix, prevent agglomeration, ensure full contact between titanium dioxide and polyamide molecular chains, and promote uniform coordination complexation reaction.

[0025] In some possible embodiments, the antioxidant is selected from one or more of hindered phenols, phosphites, thioesters, and copper salts, and is added at an amount of 0.1%-2% based on the total mass of the raw materials in the high melt strength polyamide composition. This is used to inhibit the oxidative degradation of the polyamide during processing and use, protect the integrity of the molecular chain structure, and ensure the stability of the micro-crosslinked network.

[0026] In some possible embodiments, the hindered phenolic antioxidant includes one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (1010), octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (1076), N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine (1098), and triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate] (245); In some possible implementations, phosphite antioxidants include one or more of tris[2,4-di-tert-butylphenyl]phosphite (168) and bis(2,4-dicumylphenyl)pentaerythritol-diphosphite (686); In some possible implementations, thioester antioxidants include one or more of dilauryl thiodipropionate (DLTP) and pentaerythritol tetra(3-lauryl thiopropionate) (412S). In some possible implementations, copper salt antioxidants include one or more of cuprous iodide (S5050) and cuprous bromide (H318); Secondly, this application provides a method for preparing the high melt strength polyamide composition described above, comprising the following steps: Polyamide, titanium dioxide with phosphite surface treatment, and functional additives are mixed to obtain a mixture; the mixture is added to a twin-screw extruder for melt mixing and extrusion granulation to obtain polyamide composition particles.

[0027] In some possible embodiments, the method for preparing the phosphite-treated titanium dioxide includes: mixing the titanium dioxide with the phosphite to obtain the phosphite-treated titanium dioxide; In some possible implementations, the conditions for mixing the titanium dioxide and the phosphite are: rotation speed 800~1500 r / min, temperature 60~90℃, and time 10~20 min.

[0028] In some possible implementations, the temperature of each section of the twin-screw extruder is 160~340℃, the die head temperature is 220~340℃, the screw speed is 100~1000r / min, the extrusion speed is 10~2000kg / h, and the pressure is 0.5~15MPa.

[0029] In some possible embodiments, the functional additive includes a dispersant; the step of mixing the polyamide, phosphite-surface-treated titanium dioxide, and the functional additive to obtain a mixture includes: The polyamide was dried, and the titanium dioxide with phosphite surface treatment and the dispersant were premixed to obtain a premix; the dried polyamide, the premix, and other functional additives were mixed to obtain a mixture. In some possible implementations, the polyamide is dried at a temperature of 80-120°C for 4-8 hours. In some possible implementations, the titanium dioxide and dispersant premixed with phosphite surface treatment are rotated at 1000~2000 r / min, at a temperature of 80~100℃, and for 5~10 min.

[0030] Thirdly, this application provides an application of the high melt strength polyamide composition described above or the high melt strength polyamide composition prepared according to the preparation method in the fields of injection molding, blow molding, extrusion, foaming, and 3D printing.

[0031] The polyamide composition of this application has high melt strength and good processing fluidity and mechanical properties, and can be widely used in the following fields: Injection molding: When preparing thin-walled injection molded products, there are no surface melt fracture problems or delamination problems, and the products have uniform wall thickness and good appearance; Blow molding: Preparation of films and hollow containers (such as beverage bottles, chemical storage tanks, and hydrogen storage cylinder liners), with good bubble tube stability, uniform wall thickness, and excellent mechanical properties; Extrusion processing: Used to prepare profiles and pipes (such as oil and gas pipelines, municipal pipelines, and automotive fuel lines). The melt has strong anti-sagging ability, the processing is stable, and the products have high dimensional accuracy. Foaming process: In the preparation of foamed plastics, the melt can effectively encapsulate air bubbles, resulting in dense and uniform cells, which improves the compressive strength and heat resistance of the foam material; 3D printing: As a 3D printing filament, it has high melt strength, is not easy to pull or collapse during the printing process, has strong interlayer bonding force, and high printing accuracy; Other fields: such as automotive parts (engine hoods, interior parts), electronic and electrical housings, engineering components, etc., can meet the requirements of complex processing technology for melt performance.

[0032] The technical solution of this application has the following advantages: 1. The high melt strength polyamide composition provided in this application comprises, by mass percentage, 75%~99.6% polyamide and 0.2%~24.5% functional additives; the raw materials further comprise titanium dioxide surface-treated with phosphite; the mass percentage of titanium dioxide in the surface-treated titanium dioxide is 0.005%~0.6%; the mass ratio of phosphite to titanium dioxide in the surface-treated titanium dioxide is (0.02~1):1; the particle size of the surface-treated titanium dioxide is 10~1000 nm.

[0033] This application's high melt strength polyamide composition uses titanium dioxide surface-treated with phosphite, polyamide, and functional additives in combination. The phosphite enhances the surface activity of titanium dioxide and strengthens the Ti... 4+ The coordination complexation reaction with the amide bonds of polyamide, combined with the time-temperature equivalence principle, forms a stable micro-crosslinked network structure, which significantly improves the melt strength of polyamide without significantly reducing processing fluidity. Furthermore, the optimal range for addition amount and the failure law of excessive addition have been clearly defined, and the performance remains stable during long-term use.

[0034] 2. The preparation method of the high melt strength polyamide composition provided in this application is a simple, cost-controllable, and industrially applicable technical solution, which has important practical significance and broad market application prospects. Detailed Implementation

[0035] The following embodiments are provided to better understand this application. However, the following embodiments do not constitute a limitation on the content and scope of protection of this application. Any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining the features of this application with other prior art, falls within the scope of protection of this application.

[0036] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0037] The method for preparing the high melt strength polyamide composition of this application includes the following steps: (1) Titanium dioxide surface treatment and raw material pretreatment: Titanium dioxide surface treatment: Weigh titanium dioxide and phosphite according to the ratio, add them to a high-speed mixer, and mix for 10-20 minutes at 800-1500 r / min and 60-90℃ to complete the surface treatment and obtain titanium dioxide with phosphite surface treatment.

[0038] Polyamide pretreatment: Place the polyamide raw material in a drying oven and dry it at 80-120℃ for 4-8 hours to remove moisture and avoid polyamide hydrolysis during processing; Premix preparation: Add titanium dioxide with phosphite surface treatment and dispersant to a high-speed mixer and mix for 5-10 min at 1000-2000 r / min and 80-100℃ to obtain the premix.

[0039] (2) Mixing process: Add the dried polyamide, premix, and other functional additives (antioxidants, heat stabilizers, etc.) except for the dispersant to a high-speed mixer and mix for 10-15 minutes at 80-100℃ and 500-1000r / min to ensure that all raw materials are mixed evenly.

[0040] (3) Extrusion granulation process: The uniformly mixed material is added to a twin-screw extruder for melt mixing, extrusion granulation; Temperature settings for each section of the twin-screw extruder (from feed inlet to die head): Section 1 160-340℃, Section 2 200-340℃, Section 3 220-340℃, Section 4 230-340℃, Die head temperature 220-340℃ (the specific temperature is adjusted according to the type of polyamide, such as PA12 die head temperature 220-240℃, PA66 die head temperature 250-280℃); Screw speed 100-1000 r / min, extrusion speed 10-2000 kg / h, extruder pressure 0.5-15 MPa; The extruded melt is cooled by water (water temperature 20-40℃), pelletized by a pelletizer, and screened by a vibrating screen (screen hole diameter 2-4mm) to obtain high melt strength polyamide composition particles.

[0041] The preparation method of this application is simple and has a short process. The newly added titanium dioxide surface treatment step is compatible with the existing pretreatment process. It can be industrialized using a conventional twin-screw extruder, and the production cost is controllable, making it suitable for large-scale promotion and application.

[0042] Raw material source: Polyamides: PA12 (Wanhua Chemical Wanamid® L3000, relative viscosity 2.2), PA11 (AKEMA BESNO, relative viscosity 2.2), PA6 (Xinhui Meida M2800, relative viscosity 2.8), PA66 (Shenma Nylon EPR27, relative viscosity 2.7). Titanium dioxide: anatase (particle size 50nm, 200nm), rutile (particle size 100nm, 500nm), Anada; Phosphite esters: Triphenyl phosphite (Shanghai Aladdin), Tris(2-ethylhexyl) phosphite (Guangzhou Chemical Reagent Factory), Diphenyl phosphite (Shandong Yinglang Chemical); Dispersants: KH550 (Dow Corning, USA), KH570 (Dow Corning, USA), calcium stearate (Shandong Dawn Chemical); Antioxidants: 1010 (BASF), DLTP (Shandong Yoshida Chemical); Plasticizer: BBSA (Pro-Venere); Toughening agent: MH5040 (Mitsui).

[0043] Example 1 This embodiment provides a high melt strength polyamide composition, with a total raw material mass of 100 kg, wherein: Polyamide PA12 (Wanamid® L3000): 98.3 kg (98.3%); Titanium dioxide surface-treated with phosphite: 0.6 kg (0.6%); wherein the titanium dioxide is anatase type titanium dioxide with a particle size of 50 nm, and the mass ratio of triphenyl phosphite to titanium dioxide is 0.5:1, that is, based on the mass of titanium dioxide in the phosphite-treated titanium dioxide, the mass content in the raw material is 0.4%; Dispersant KH550: 0.3 kg (0.3%); Antioxidant 1010: 0.4 kg (0.4%); Antioxidant DLTP: 0.4 kg (0.4%).

[0044] The preparation method of the high melt strength polyamide composition in this embodiment includes the following steps: 1) Titanium dioxide surface treatment: Add titanium dioxide and triphenyl phosphite to a high-speed mixer and mix at 1200 r / min and 80℃ for 15 min to obtain titanium dioxide with phosphite surface treatment. Raw material pretreatment: PA12 was dried at 100℃ for 6 hours; titanium dioxide with phosphite surface treatment and dispersant KH550 were added to a high-speed mixer and mixed at 1500 r / min and 90℃ for 8 minutes to obtain a premix; 2) Mixing: Add the dried polyamide, premix and antioxidant to a high-speed mixer and mix at 90℃ and 800r / min for 12min; 3) Extrusion granulation: The uniformly mixed material from step 2) is added to a twin-screw extruder for melt mixing and extrusion granulation; the temperature of each section of the twin-screw extruder (from the feed port to the die head) is 180℃, 220℃, 240℃, 260℃, 240℃, the screw speed is 200r / min, the extrusion speed is 30kg / h, the pressure is 2MPa, water cooling pelletizing, and drying are used to obtain composite granules.

[0045] Example 2 Polyamide composition formulation (total mass 100kg): Polyamide PA11 (AKEMA BESNO): 97.7 kg (97.7%); Titanium dioxide surface-treated with phosphite: 0.3 kg (0.3%); wherein the titanium dioxide is rutile titanium dioxide with a particle size of 100 nm, and the mass ratio of tris(2-ethylhexyl) phosphite to titanium dioxide is 0.5:1, that is, based on the mass of titanium dioxide in the phosphite-treated titanium dioxide, its mass content in the raw material is 0.2%; Dispersant calcium stearate: 1.0 kg (1.0%); Antioxidant 1010: 0.6 kg (0.6%); Antioxidant DLTP: 0.4 kg (0.4%); The preparation method of the high melt strength polyamide composition in this embodiment includes the following steps: 1) Titanium dioxide surface treatment: Titanium dioxide and tris(2-ethylhexyl) phosphite are added to a high-speed mixer and mixed at 1000 r / min and 70°C for 18 min to obtain titanium dioxide with phosphite surface treatment. Raw material pretreatment: PA11 was dried at 110℃ for 5 hours; titanium dioxide with phosphite surface treatment and calcium stearate dispersant were added to a high-speed mixer and mixed at 1800 r / min and 85℃ for 10 minutes to obtain a premix. 2) Mixing: Add the dried polyamide, premix and antioxidant to a high-speed mixer and mix at 85℃ and 900r / min for 10min; 3) Extrusion granulation: Add the uniformly mixed material from step 2) into a twin-screw extruder for melt mixing and extrusion granulation; the temperature of each section of the twin-screw extruder is 190℃, 230℃, 240℃, 260℃, 240℃, screw speed is 250r / min, extrusion speed is 25kg / h, pressure is 2.5MPa, and water cooling pelletizing is used.

[0046] Example 3 Polyamide composition formulation (total mass 100kg): Polyamide PA66 (EPR27): 99.58 kg (99.58%); Titanium dioxide surface-treated with phosphite: 0.02 kg (0.02%); wherein, the titanium dioxide is anatase type titanium dioxide with a particle size of 200 nm, and the mass ratio of triphenyl phosphite to titanium dioxide is 1:1, that is, based on the mass of titanium dioxide in the phosphite-treated titanium dioxide, the mass content in the raw material is 0.01%; Dispersant KH560: 0.1 kg (0.1%); Antioxidant 1010: 0.3 kg (0.3%); Preparation method: 1) Titanium dioxide surface treatment: Add titanium dioxide and triphenyl phosphite to a high-speed mixer and mix at 800 r / min and 60℃ for 20 min to obtain titanium dioxide with phosphite surface treatment; Raw material pretreatment: PA66 was dried at 120℃ for 4 hours; titanium dioxide with phosphite surface treatment was mixed with dispersant KH560 at high speed (2000r / min, 100℃, 5min) to obtain a premix; 2) Mixing: Add the dried polyamide, premix and antioxidant to a high-speed mixer and mix at 100℃ and 1000r / min for 10min; 3) Extrusion granulation: Add the uniformly mixed material from step 2) into a twin-screw extruder for melt mixing and extrusion granulation; the temperature of each section of the twin-screw extruder is 200℃, 230℃, 260℃, 280℃, 260℃, the screw speed is 180r / min, the extrusion speed is 20kg / h, and the pressure is 3MPa.

[0047] Example 4 Polyamide composition formulation (total mass 100kg): Polyamide PA6 (M2800): 96.9 kg (96.9%); Titanium dioxide surface-treated with phosphite: 1.1 kg (1.1%); wherein the titanium dioxide is rutile titanium dioxide with a particle size of 500 nm, and the mass ratio of diphenyl phosphite to titanium dioxide is 5:6, that is, based on the mass of titanium dioxide in the phosphite-treated titanium dioxide, its mass content in the raw material is 0.6%). Dispersant KH570: 1.0 kg (1.0%); Antioxidant 1010: 0.5 kg (0.5%); Antioxidant DLTP: 0.5 kg (0.5%); Preparation method: 1) Titanium dioxide surface treatment: Add titanium dioxide and diphenyl phosphite to a high-speed mixer and mix at 1500 r / min and 90℃ for 10 min to obtain titanium dioxide with phosphite surface treatment. Raw material pretreatment: PA6 was dried at 80℃ for 8 hours; titanium dioxide with phosphite surface treatment was mixed with dispersant KH570 at high speed (1200r / min, 95℃, 10min) to obtain a premix; 2) Mixing: Add the dried polyamide, premix and antioxidant to a high-speed mixer and mix at 95℃ and 700r / min for 15min; 3) Extrusion granulation: Add the uniformly mixed material from step 2) into a twin-screw extruder for melt mixing and extrusion granulation; the temperature of each section of the twin-screw extruder is 180℃, 220℃, 240℃, 260℃, 240℃, the screw speed is 220r / min, the extrusion speed is 35kg / h, and the pressure is 1.5MPa.

[0048] Example 5 This embodiment provides a high melt strength polyamide composition, with a total raw material mass of 100 kg, wherein: Polyamide PA12 (Wanamid® L3000): 88.3 kg (88.3%); Titanium dioxide surface-treated with phosphite: 0.6 kg (0.6%); wherein the titanium dioxide is anatase type titanium dioxide with a particle size of 50 nm, and the mass ratio of triphenyl phosphite to titanium dioxide is 0.5:1, that is, based on the mass of titanium dioxide in the phosphite-treated titanium dioxide, the mass content in the raw material is 0.4%; Dispersant KH550: 0.3 kg (0.3%); Antioxidant 1010: 0.4 kg (0.4%); Antioxidant DLTP: 0.4 kg (0.4%); Toughening agent MH5040: 10kg (10%).

[0049] The preparation method of the high melt strength polyamide composition in this embodiment is the same as that in Example 1.

[0050] Example 6 This embodiment provides a high melt strength polyamide composition, with a total raw material mass of 100 kg, wherein: Polyamide PA12 (Wanamid® L3000): 75kg (75%); Titanium dioxide surface-treated with phosphite: 0.6 kg (0.6%); wherein the titanium dioxide is anatase type titanium dioxide with a particle size of 50 nm, and the mass ratio of triphenyl phosphite to titanium dioxide is 0.5:1, that is, based on the mass of titanium dioxide in the phosphite-treated titanium dioxide, the mass content in the raw material is 0.4%; Dispersant KH550: 0.3 kg (0.3%); Antioxidant 1010: 0.4 kg (0.4%); Antioxidant DLTP: 0.4 kg (0.4%); Plasticizer BBSA: 13.3 kg (13.3%); Toughening agent MH5040: 10kg (10%).

[0051] The preparation method of the high melt strength polyamide composition in this embodiment is the same as that in Example 1.

[0052] Comparative Example 1 This comparative example provides a polyamide composition with a total raw material mass of 100 kg, wherein: Polyamide PA12 (Wanamid® L3000): 98.9 kg (98.9%); Dispersant KH550: 0.3 kg (0.3%); Antioxidant 1010: 0.4 kg (0.4%); Antioxidant DLTP: 0.4 kg (0.4%); The preparation method of this comparative polyamide composition includes the following steps: 1) Raw material pretreatment: PA12 was dried at 100℃ for 6 hours; 2) Mixing: Add the dried polyamide, dispersant and antioxidant to a high-speed mixer and mix at 90℃ and 800r / min for 12min; 3) Extrusion granulation: The uniformly mixed material from step 2) is added to a twin-screw extruder for melt mixing and extrusion granulation; the temperature of each section of the twin-screw extruder (from the feed port to the die head) is 180℃, 220℃, 240℃, 300℃, and 240℃, the screw speed is 200r / min, the extrusion speed is 30kg / h, the pressure is 2MPa, water cooling pelletizing is performed, and the composite granules are obtained after drying.

[0053] Comparative Example 2 This comparative example provides a polyamide composition with a total raw material mass of 100 kg, wherein: Polyamide PA12 (Wanamid® L3000): 98.5 kg (98.5%); Anatase titanium dioxide (same as Example 1, untreated): 0.4 kg (0.4%). Dispersant KH550: 0.3 kg (0.3%); Antioxidant 1010: 0.4 kg (0.4%); Antioxidant DLTP: 0.4 kg (0.4%); The preparation method of this comparative polyamide composition is basically the same as that of Example 1, except that there is no titanium dioxide surface treatment step, and the untreated titanium dioxide is directly mixed with the dispersant.

[0054] Comparative Example 3 This comparative example provides a polyamide composition with a total raw material mass of 100 kg, wherein: polyamide PA12 (Wanamid® L3000): 97.8 kg (97.8%). Titanium dioxide surface-treated with phosphite: 1.1 kg (1.1%); wherein the titanium dioxide is anatase type titanium dioxide with a particle size of 50 nm, and the mass ratio of triphenyl phosphite to titanium dioxide is 3:8, that is, based on the mass of titanium dioxide in the phosphite-treated titanium dioxide, its mass content in the raw material is 0.8%). Dispersant KH550: 0.3 kg (0.3%); Antioxidant 1010: 0.4 kg (0.4%); Antioxidant DLTP: 0.4 kg (0.4%); The preparation method of this comparative polyamide composition is the same as that in Example 1.

[0055] Comparative Example 4 This comparative example provides a polyamide composition with a total raw material mass of 100 kg, wherein: Polyamide PA12 (Wanamid® L3000): 98.3 kg (98.3%); Anatase titanium dioxide (particle size 50nm): 0.4kg (0.4%). Phosphite (triphenyl phosphite): 0.2 kg (0.2%); Dispersant KH550: 0.3 kg (0.3%); Antioxidant 1010: 0.4 kg (0.4%); Antioxidant DLTP: 0.4 kg (0.4%); The preparation method of this comparative polyamide composition includes the following steps: 1) Raw material pretreatment: PA12 was dried at 100℃ for 6 hours; 2) Mixing: Add all raw materials to a high-speed mixer and mix at 90℃ and 800r / min for 12min; 3) Extrusion granulation: The uniformly mixed material from step 2) is added to a twin-screw extruder for melt mixing and extrusion granulation; the temperature of each section of the twin-screw extruder (from the feed port to the die head) is 180℃, 220℃, 240℃, 300℃, and 240℃, the screw speed is 200r / min, the extrusion speed is 30kg / h, the pressure is 2MPa, water cooling pelletizing is performed, and the composite granules are obtained after drying.

[0056] Performance testing methods: (1) The melt strength of the polyamide composition was determined using a capillary rheometer (Instron 3211) coupled with a Gottfer Rheotens 71.97 melt tensile rheometer: The polyamide composition particles were added to the barrel of a capillary rheometer and heated to 260°C, held at that temperature for 5 minutes to allow it to fully melt. The capillary rheometer piston was then started, operating at a shear rate of 30 s⁻¹. -1 The melt is extruded from a capillary die (1 mm diameter, L / D ratio L / D = 20 / 1). The extruded melt strip immediately enters the traction roller of the melt stretch rheometer below (the traction roller is positioned 100 mm below the die at a fixed distance), and the traction roller accelerates at a constant speed of 100 mm / s². 2 The material strip is accelerated from zero speed until it breaks. The maximum tensile force (in mN) measured by the sensor before breakage is recorded; this value is the melt strength.

[0057] (2) Shear viscosity: The capillary rheometer (Instron 3211) with a die diameter of 1 mm and an aspect ratio of 20:1 was used for testing. The specific steps included: test temperature of 300℃ and shear rate of 100 s. -1 .

[0058] The polyamide composition particles were added to the barrel of a capillary rheometer and heated to 300°C, held at that temperature for 5 minutes to allow for complete melting. The capillary rheometer piston was then started, operating at a shear rate of 100 s⁻¹. -1 The melt is extruded from the capillary die, and the pressure value ΔP is recorded after 15 seconds. The shear viscosity η is calculated according to the following formula. The test is repeated 3 times, and the arithmetic mean is taken as the final result.

[0059] η=(ΔP×D) / (4L×γ˙) in: η—shear viscosity, Pa·s; ΔP—Recorded pressure value, Pa; ΔP is the difference between the melt pressure (measured by the pressure sensor) inside the barrel and directly in front of the die inlet and the pressure at the die outlet (taken as 0 Pa); D—Diameter of the die, in meters; L—Die length, in meters; γ˙—shear rate, s -1 .

[0060] (3) Processing fluidity: The polyamide composition particles were dried in a vacuum oven at 90°C for 12 hours. The melt flow rate of the polyamide composition was measured using a melt flow rate (MFR) tester at 275°C and 2.16 kg load, and the MFR value was recorded. (4) Tensile strength: Tensile strength was determined using a universal testing machine. The specimen was a type 1A dumbbell-shaped specimen (with dimensions of the parallel section in the middle: length ≥ 75 mm, width 10 ± 0.5 mm, thickness 4 ± 0.2 mm). The testing speed was 5 mm / min. The specimen was conditioned for at least 88 hours at 23 ± 2℃ and 50 ± 5% RH (relative humidity) before testing. Tensile strength was calculated using the formula σ = F. max / A0 calculation, F max —Maximum tensile force (maximum force before fracture or at yield), N; A0—Initial cross-sectional area of ​​the specimen, mm 2 .

[0061] (5) Impact strength: The notched impact strength was determined using a simply supported beam pendulum impact testing machine. The specimen dimensions were 80 mm × 10 mm × 4 mm, with a V-notch (angle 45°, root radius 0.25 mm) and a remaining notch width of 8.0 mm. Conditioning conditions were 23±2℃ and 50±5%RH for 88 hours. The pendulum energy was 2 J, the support span was 62 mm, and the impact velocity was 2.9 m / s. The impact strength was calculated using the formula a = E. c / (h×b N Calculation, unit kJ / m 2 E c —Sample fracture absorption energy after friction loss correction, J; h—Sample thickness, mm; b N — Remaining notch width (sample width minus notch depth), mm; average value of 10 samples per group.

[0062] (6) Titanium dioxide dispersibility: The microstructure of titanium dioxide particles was observed by transmission electron microscopy (TEM). Agglomerated particles were defined based on the original particle size of a single particle (i.e., the particle size of the titanium dioxide raw material used): aggregates consisting of two or more original titanium dioxide particles that are mutually attached, fused at the interface, or tightly packed, and whose overall equivalent particle size is greater than 1.5 times the average particle size of the original particles, were identified as agglomerated particles. Image processing software was used to perform threshold segmentation and particle identification of the TEM field of view. The total area of ​​all titanium dioxide particles and the area of ​​agglomerated particles were counted separately, and the area ratio of agglomerated particles was calculated. At least 5 independent fields of view were randomly selected and the average value was taken. This ratio was used to quantitatively evaluate the degree of dispersion and agglomeration of titanium dioxide in the resin matrix.

[0063] (7) Long-term stability: After the polyamide composition particles are placed for 6 months, the melt strength and mechanical properties are tested again to evaluate the performance degradation.

[0064] The test results are shown in Table 1.

[0065] Table 1 Performance of Examples

[0066] Table 2 Comparative Performance

[0067] Performance comparison analysis between the examples and comparative examples: Melt strength: The melt strength of Examples 1-6 was 148-197 mN, which was significantly improved compared with Comparative Examples 1-4. The maximum value of 197 mN was reached when the titanium dioxide content was 0.4%.

[0068] Dispersibility and Reactivity: The proportion of agglomerated particles in titanium dioxide (Examples 1-6) treated with phosphite was <8%, while the proportion of agglomerated particles in untreated or directly added phosphite Comparative Examples 2 and 4 was >18%, demonstrating that surface treatment can significantly improve dispersibility and enhance Ti reactivity. 4+ Reactivity.

[0069] Processing fluidity: The MFR of Examples 1-6 was 10.2-16.5 g / 10 min, maintaining good processing fluidity, while the processing fluidity of Comparative Example 3 (MFR=6.8 g / 10 min) deteriorated significantly, making it difficult to meet the requirements of industrial processing.

[0070] Mechanical properties: The tensile strength of Example 1 is 53 MPa, and the impact strength is 13 kJ / m. 2 Compared with Comparative Examples 1-4, the composition of this application improves melt strength without compromising the mechanical properties of polyamide.

[0071] Long-term stability: After 6 months of storage, the melt strength and mechanical properties of Examples 1-6 showed almost no decline, demonstrating the stability of the dynamic micro-crosslinked network. In contrast, the performance of the untreated titanium dioxide in Comparative Example 2 showed a significant decline, proving the effect of surface treatment on stability.

[0072] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this application.

Claims

1. A high melt strength polyamide composition, characterized in that, The raw materials of the high melt strength polyamide composition, by weight percentage, include 75% to 99.6% polyamide and 0.2% to 24.5% functional additives; The raw materials also include titanium dioxide that has been surface-treated with phosphite; The method for preparing the titanium dioxide with phosphite surface treatment includes: mixing the titanium dioxide with the phosphite to obtain the titanium dioxide with phosphite surface treatment; The mass percentage of titanium dioxide in the titanium dioxide surface-treated with phosphite is 0.01% to 0.6% in the raw material. In the titanium dioxide surface treated with phosphite, the mass ratio of phosphite to titanium dioxide is (0.5~1):1; The titanium dioxide in the phosphite-treated titanium dioxide has a particle size of 50~500nm.

2. The high melt strength polyamide composition according to claim 1, characterized in that, The polyamide has a relative viscosity of 1.4 to 3.4; And / or, the polyamide includes repeating units -[NH-R1-CO]- and / or -[NH-R2-NH-CO-R3-CO]-; wherein R1, R2, and R3 are each independently selected from one or more of alkylene, alicyclic, and aromatic groups.

3. The high melt strength polyamide composition according to claim 1, characterized in that, The polyamide has a relative viscosity of 2.2 to 2.

8.

4. The high melt strength polyamide composition according to any one of claims 1-3, characterized in that, The polyamide includes one or more of the following: polydodecanamine, polyundecanolactam, polydodecanediamine, polydodecanediamine, polyhexamethylenediamine, polyhexamethylenediamine, polycaprolactam, polyhexamethylenediamine, polypentanediamine, polyhexadecanediamine, polyhexadecanediamine, polyhexadecanediamine, polydodecanediamine, polydodecanediamine, polydodecanoediamine, poly[bis(3-methyl-4-aminocyclohexyl)methane-alt-dodecanodiamide], poly[bis(4-aminocyclohexyl)methane-alt-dodecanodiamide], poly[bis(4-aminocyclohexyl)methane-alt-undecanodiamide], poly(m-phenylene adipamide), poly(hexamethylene terephthalamide), poly(hexamethylene terephthalamide), poly(nonadiamine), poly(decanodiamine), and poly(dodecanodiamine). And / or, the phosphite includes one or more of the following: triphenyl phosphite, trioctyl phosphite, tri(2-ethylhexyl) phosphite, diphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol diphosphite (2,4-di-tert-butylphenol), and phenyl diisooctyl phosphite. And / or, the titanium dioxide includes one or both of anatase titanium dioxide and rutile titanium dioxide; And / or, the functional additives include one or more of the following: dispersants, antioxidants, light aging resistant additives, heat stabilizers, lubricants, antistatic agents, fillers, pigments, flame retardants, plasticizers, and toughening agents.

5. The high melt strength polyamide composition according to claim 4, characterized in that, The dispersant includes one or more of the following: silane coupling agent, calcium stearate, zinc stearate, polyethylene wax, polypropylene wax, Montan wax, rice bran wax, and vinyl bis-stearamide; And / or, based on the total mass of the raw materials of the high melt strength polyamide composition, the mass content of the dispersant is 0.02~3%.

6. A method for preparing a high melt strength polyamide composition according to any one of claims 1-5, characterized in that, Includes the following steps: Polyamide, titanium dioxide with phosphite surface treatment, and functional additives are mixed to obtain a mixture; the mixture is added to a twin-screw extruder for melt mixing and extrusion granulation to obtain polyamide composition particles.

7. The method for preparing the high melt strength polyamide composition according to claim 6, characterized in that, The conditions for the mixing process are: rotation speed 800~1500 r / min, temperature 60~90℃, and time 10~20 min.

8. The method for preparing the high melt strength polyamide composition according to any one of claims 6-7, characterized in that, At least one of the following conditions must be met: (1) The temperature of the twin-screw extruder is 160~340℃, the die head temperature is 220~340℃, the screw speed is 100~1000r / min, the extrusion speed is 10~2000kg / h, and the pressure is 0.5~15MPa; (2) The functional additives include dispersants; the step of mixing polyamide, titanium dioxide with phosphite surface treatment, and functional additives to obtain a mixture includes: The polyamide was dried, and titanium dioxide with a phosphite surface treatment and a dispersant were premixed to obtain a premix; The dried polyamide, premix, and other functional additives are mixed to obtain a mixture.

9. The application of the high melt strength polyamide composition according to any one of claims 1-5 or the high melt strength polyamide composition prepared by the preparation method according to any one of claims 6-8 in the fields of injection molding, blow molding, extrusion, foaming, and 3D printing.

Citation Information

Patent Citations

  • Polyamide composition with high heat resistance and high melt strength

    CN112175388A

  • Toughened polyamide material with high melt strength as well as preparation method and application thereof

    CN119798978A